Lateral Approach Sinus (LAS) and Crestal Approach Sinus (CAS): The Unravelled Paraphernalia for Maxillary Sinus Membrane Advancement (Global Journal of Medical Research, 2023)
The permanent replacement of missing teeth in the maxillary posterior tooth region becomes a tedious task when it is confounded with bone atrophies. To overcome this problem and achieve successful rehabilitation, maxillary sinus membrane elevation procedures have been advocated as the most reliable means. The lateral window technique and the crestal approach are two of the most common approaches. These technologically developed procedures have reported high success rates in cases of deficient residual bone. Over time, there have been many advancements in these techniques that led to the development of user-friendly kits like the Lateral approach Sinus (LAS) kit and the Crestal approach Sinus (CAS) kit. In this case series, we have reported two cases, treated with either of these approaches and have compared the same.
Keywords: crestal approach sinus lift; hard tissue augmentation; lateral window approach sinus lift